The use of a rights-based approach to address juvenile violence in Australian schools: from policy to practice - Monterosso, Stephen (Curtin University, 2015)
While school violence is an issue that is of a longstanding historical nature, increased levels of lethality evident in episodic school violence in contemporary society has generated collective concern. Australia is hardly immune from this escalation although fatalities have been fortuitously infrequent, unlike in several overseas locations. This thesis will address the issue of juvenile violence in school settings from an Australian viewpoint which is grounded in restorative justice practises that advance juvenile human rights.